2015
DOI: 10.4081/ijas.2015.3870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Turmeric Rhizome Extract on Growth Performance, Carcass Characteristics, Antioxidant Capability, and Meat Quality of Wenchang Broiler Chickens

Abstract: Our study aimed to determine the effect of increasing dietary levels of turmeric rhizome extract (TRE) on performance, carcass characteristics, antioxidant capability and meat quality of Wenchang broiler chickens. Three hundred, 1-day-old Wenchang broiler chickens were brooded together for 2 weeks, then randomly allocated into four treatments with five replicates of 15 birds each. Birds were fed a corn-soybean basal diet supplemented with TRE at 0, 100, 200 and 300 mg/kg for 12 weeks. The results revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
68
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 27 publications
19
68
1
5
Order By: Relevance
“…Hosseini-Vashan et al (2012), also reported that feeding turmeric powder did not affect weigh gain, feed intake, feed conversion ratio and production index of broiler chickens. Concomitantly, Wang et al (2015) reported that turmeric rhizome extract had no significant effect on the body weight of Wenchang broiler chickens. The exact rationale for the discrepancy results above remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hosseini-Vashan et al (2012), also reported that feeding turmeric powder did not affect weigh gain, feed intake, feed conversion ratio and production index of broiler chickens. Concomitantly, Wang et al (2015) reported that turmeric rhizome extract had no significant effect on the body weight of Wenchang broiler chickens. The exact rationale for the discrepancy results above remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in agreement with Durrani et al (2006) showing a higher relative weight of breast and thigh meats in turmeric powder fed broilers. Concomitantly, Decocted Turmeric for Broiler Chicks (I. Isroli et al) 267 Wang et al (2015) reported that supplementation with turmeric rhizome extract increased the absolute and relative weight of breast muscle of Wenchang broiler chickens. Regarding the negative effect of decocted turmeric, when provided at 100% in the drinking water, on the weight of breast muscle, this result was in contrast to the most of published reports earlier (HosseiniVashan et al, 2012;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For the entire assays in the whole blood and serum, the intra-assay and inter-assay coefficients of variation of the control samples were 1.5-4.8 and 2.7-5.4 %, respectively. Drip loss of meat was measured according to Wang et al (2015) with a few modifications. Around 45 min after slaughter, the breast or thigh muscles were weighed and the pH was measured.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…Alagawany et al (2015) studied the effect of turmeric (0.5%) in broiler chickens and they recorded that catalase (CAT), SOD activities and GSH concentration were significantly increased due to turmeric. Turmeric extract was increased the enzymatic activities of SOD and glutathione peroxidase, and reduced MDA concentrations, compared to the control group (Wang et al, 2015). Nadia et al (2008) reported a lower MDA formation in the egg yolk of laying hens fed turmeric in concentrations of 1 and 5 g/kg during the laying period.…”
Section: Discussionmentioning
confidence: 99%